Introduction to the dossier "What’s left of left populism? Theoretical and empirical reappraisals" - Mazzolini, Samuele (Res Publica. Revista de Historia de las Ideas Políticas, 2025)
This dossier gathers a selection of revised and edited contributions stemming from the conference “What’s Left of Left Populism? Theoretical and Empirical Reappraisals”, held at the Catholic University of Milan on 23–24 May 2024. The conference, which convened scholars from political science, theory, and philosophy, fostering a rich interdisciplinary dialogue, aimed to scrutinise the validity and contemporary relevance of the left populist hypothesis as a strategic blueprint for progressive politics. It took place at a moment in which left populist strategies appear to have come to a standstill, offering a forum for interdisciplinary reflection on the historical trajectories, theoretical foundations, ibridations and impasses, and practical pros and cons of left populism. Particular attention was given to European and Latin American experiences, while theoretically the dossier significantly engages with the enduring work of Ernesto Laclau and Chantal Mouffe.